SHORT REVIEW OF PATHOPHYSIOLOGY OF CATECHOL ESTROGEN - ., Rajnee; Choudhary, Sunita; Binawara, Bijendra Kumar (Pakistan Journal of Physiology, 2010)
In women of reproductive age, the primary source of circulating estrogens is the ovaries. There are three forms of estrogen circulating in our bloodstream: estradiol, estrone and estriol. The normal ratio of these three types of estrogens ideally should be 10–20%, 10–20%, and 60–80% respectively. The estrogen that accounts for most of the tissue stimulation is called estradiol. Estrone is a little bit less potent with estriol being the weakest. Brain converts estrone and estradiol to 2- and 4-hydroxylated derivatives known as catechol estrogens